Ben Robinson in conversation with Jerome Carson. Issue 1 (12th February 2018) - Robinson, Ben; Carson, Jerome
Abstract : Purpose: The purpose of this paper is to provide a profile of Ben Robinson. Design/methodology/approach: Ben provides a short summary of his life and is then interviewed by Jerome. Findings: Ben talks about his inpatient treatment for anorexia and his long journey of recovery. Research limitations/implications: Single case studies provide us with unique insights into the lived experience of people with mental health problems. They often provide us with hints as to how services could be improved. Practical implications: Ben argues that the voice of service users needs to be heard more by professionals. "The only experts of a mental health problem are the people who have been through a mental health issue themselves". Social implications: One of the classic recovery reports talked about "going the extra mile". Ben talks about how his family therapist would visit him at the end of her working day. As he says, "this was something she didn't have to do, but wanted to do as she genuinely cared for us". Originality/value: Ben is determined to use his experiences for the benefit of others. Even to have helped a single person will be his biggest life achievement.